2020
DOI: 10.1002/aepp.13090
|View full text |Cite
|
Sign up to set email alerts
|

Labor Issues in the Food Supply Chain Amid the COVID‐19 Pandemic

Abstract: The impacts of COVID‐19 on labor in the food supply chain and on workers’ decisions to accept essential jobs are discussed. We then analyze surveys administered to low‐skilled domestic workers before and during the pandemic to assess respondents' attitudes toward food production, guest workers, immigration policy, and the government's response to COVID‐19. Results suggest the outbreak resulted in respondents, on average, shifting their view toward food being a national security issue and a higher degree of emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
67
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 96 publications
(92 citation statements)
references
References 4 publications
(3 reference statements)
1
67
0
4
Order By: Relevance
“…According to the US Centers for Disease Control and Prevention, 9% of US meat plant workers were infected with COVID-19 from late March to May 2020, with outbreaks occurring at 239 meat and poultry processing facilities (Waltenberg et al, 2020;Weersink et al, 2021). 2 While not as severe as in the United States, workforce outbreaks at meat processing plants were reported across a number of other countries, including Canada, Brazil, and in Europe (Aday & Aday, 2020;Luckstead et al, 2021;Tonsor & Schulz, 2020;Weersink et al, 2021). The beef packing sector in Canada is highly concentrated, with three packing plants accounting for 85% of slaughter capacity.…”
Section: 2mentioning
confidence: 99%
See 2 more Smart Citations
“…According to the US Centers for Disease Control and Prevention, 9% of US meat plant workers were infected with COVID-19 from late March to May 2020, with outbreaks occurring at 239 meat and poultry processing facilities (Waltenberg et al, 2020;Weersink et al, 2021). 2 While not as severe as in the United States, workforce outbreaks at meat processing plants were reported across a number of other countries, including Canada, Brazil, and in Europe (Aday & Aday, 2020;Luckstead et al, 2021;Tonsor & Schulz, 2020;Weersink et al, 2021). The beef packing sector in Canada is highly concentrated, with three packing plants accounting for 85% of slaughter capacity.…”
Section: 2mentioning
confidence: 99%
“…At the time of writing the 2020 paper (Hobbs, 2020), a few meat packing plants in the United States had begun experiencing problems. The situation changed rapidly through April 2020, and by late April, over 30 US meat processing facilities had closed due to workforce outbreaks of COVID‐19 (Luckstead et al., 2021), with outbreaks also emerging at major Canadian meat processing facilities. Daily processing volumes of beef and pork in the United States were about 40% below 2019 levels through the last week of April and first week of May 2020, with federally inspected slaughter volumes averaging 22% below 2019 levels over the 2‐month period from early April to early June (Lusk et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some states, like California, have extended economic safety nets to unauthorized immigrants during the pandemic, though some potential recipients have said that they are fearful of exposing their immigration status by claiming benefits. A recent survey of low‐skilled domestic workers indicated that the coronavirus pandemic led many of them to empathize more with H‐2A workers but did not change political views regarding immigration policy (Luckstead, Nayga Jr., and Snell 2020).…”
Section: Conclusion With a Look To The Futurementioning
confidence: 99%
“…Nevertheless, if farm labor becomes scarcer, costlier, or less reliable, the economic advantages of mechanization are expected to rise. Studies suggest that one outcome of the coronavirus pandemic is that people are increasingly concerned about national food security, which may increase consumer demand for domestically produced fruits and vegetables (Luckstead, Nayga Jr., and Snell 2020). Another likely outcome is increased innovations that make the food supply chain more resilient to global shocks, including new production methods that reduce seasonal farm labor demand but also create higher‐skilled, higher‐paying, safer farm jobs.…”
Section: Conclusion With a Look To The Futurementioning
confidence: 99%